Dampak Budaya Adaptif dan Ideasional dalam Kasus Stunting di Indonesia - Teguh, Monika; Koesbardiati, Toetik; Ida, Rachmah; Puspa, Ratih; Syafarani, Yavrina (Jurnal Aspirasi, 2023)
Stunting is a form of malnutrition that occurs as a result of improper child- rearing practices that cause a child to lack nutrition from the womb until the first thousand days of life. In 2021, 24.4% of Indonesian toddlers still experience stunting. One of the causes is a culture that is not in line with healthy living behaviors. This study will answer the question of what culture has an impact on the stunting cases in Indonesia? The research method used is descriptive qualitative with literature study as the basis for its data. The results of the research show various cultural roles both adaptive and ideational cultures that contribute to stunting. Adaptive cultures that play a role in stunting include hustle culture, working mothers, and education. Meanwhile, ideational cultures that still have an impact on stunting until now include beliefs, early marriage, incorrect feeding, and incorrect feeding methods. It is hoped that the results of this study can provide a contribution to the study of public health and more effective health promotion in the future. AbstrakStunting merupakan kasus kekerdilan yang terjadi akibat kesalahan pola asuh anak yang menyebabkan anak kekurangan gizi sejak dari dalam kandungan sampai seribu hari pertama kehidupan. Pada tahun 2021 masih terdapat 24,4 persen anak balita yang mengalami stunting di Indonesia. Salah satu penyebabnya adalah budaya masyarakat yang tidak sesuai dengan perilaku hidup sehat. Studi ini akan menjawab pertanyaan budaya apa yang berdampak terhadap kasus stunting di Indonesia? Metode penelitian yang digunakan adalah kualitatif deskriptif dengan studi literatur sebagai dasar datanya. Hasil dari penelitian menunjukkan berbagai peranan budaya baik budaya adaptif maupun budaya ideasional yang turut mendorong terjadinya stunting. Budaya adaptif yang berperan dalam terjadinya stunting antara lain hustle culture, ibu bekerja, dan pendidikan. Sementara itu, budaya ideasional yang juga masih berpengaruh terhadap terjadinya stunting sampai saat ini antara lain kepercayaan, pernikahan dini, kesalahan pemberian makanan, dan kesalahan cara pemberian makanan. Diharapkan hasil penelitian ini dapat memberikan sumbangsih bagi kajian kesehatan masyarakat dan promosi kesehatan yang lebih efektif ke depannya.